PRESENCE OF AVIAN INFLUENZA VIRUS IN WILD BIRDS IN THE WETLANDS OF PUERTO VIEJO, LIMA - Segovia H., Karen (2013)
The objective of the study was to detect the presence of avian influenza (AI) virus in wild aquatic birds found in Puerto Viejo wetlands, Lima-Peru. Fresh faecal samples (n=900) from 18 species of wild birds were collected from April 2008 to February 2009. Samples were analyzed by virus isolation in SPF embryonated chicken eggs. Seven strains of low pathogenicity AI viruses subtype H12N5 were isolated; six from the migratory species Arenaria interpres, and one from the resident species Fulica ardesiaca. The technique of risk assessment using Monte Carlo Simulation (program @ risk) indicated that the probability of finding the AI virus in wild birds from Puerto Viejo wetlands was 0.88% with a confidence interval of 0.15 to 2.53%. The results of the study showed that wild birds from Puerto Viejo wetlands constitute a reservoir for avian influenza virus in Peru.